The enforcement of socio-economic rights in the African human rights system : drawing inspiration from the International Covenant on Economic, Social and Cultural Rights and South Africa's evolving jurisprudence - Mbazira, Christopher (University of Pretoria, 2006)
Prepared under the supervision of Professor Sandra Liebenberg at the Faculty of Law, University of the Western Cape, South Africa